Prophylaxis of Post–Endoscopic Retrograde Cholangiopancreatography Pancreatitis Using Temporary Pancreatic Stents Versus Rectal Nonsteroidal Anti-inflammatory Drugs: A Randomized Controlled Trial. Issue 6 (13th July 2022) - Koshitani, Tatsuya; Konaka, Yoshitomo; Ohishi, Takashi; Yasuda, Tomoyo; Morinushi, Tatsuo; Mita, Masaki; Masuda, Masataka; Nakano, Keimei; Fuki, Shuichi; Nakagawa, Shuji
Abstract : Objectives: Both pancreatic stenting and rectal nonsteroidal anti-inflammatory drugs (NSAIDs) prevent post–endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. The aim of the study was to compare post-ERCP pancreatitis (PEP) prophylaxis using pancreatic stents and/or rectal NSAIDs prospectively. Methods: A total of 321 patients undergoing ERCP were studied. Each patient was randomly allocated to receive pancreatic stent placement (PS), 50 mg of rectal diclofenac (NSAID), or both (PS + NSAID) for PEP prophylaxis. The primary outcome was the occurrence rate of PEP, and secondary outcomes included the severity of PEP and serum pancreatic amylase and lipase levels on the day after ERCP. Results: Five patients (PS: 2/101, NSAID: 1/106, PS + NSAID: 2/102) developed PEP, and the overall occurrence rate of PEP was 1.6% (5/309). The occurrence rates of PEP in the PS, NSAID, and PS + NSAID groups were statistically equivalent with an equivalent margin of 10%. The severity of PEP was mild in all 5 patients. Median serum pancreatic amylase and lipase levels in the NSAID group were significantly lower than those in the PS and PS + NSAID groups. Conclusions: Rectal administration of 50 mg of diclofenac may become a first-line therapy for PEP prophylaxis in our country.